Self-Oscillators Based on Surface Acoustic Waves (A Review) - V. A. Loiko; A. A. Dobrovolsky; V. N. Kochemasov; A. R. Safin (Известия высших учебных заведений России: Радиоэлектроника, 2022)
Introduction. Modern precision radio systems impose stringent requirements on the quality of the reference signal sources used. Various approaches are used to create sources of reference signals in the microwave range – micro-wave self-oscillators (SO). A promising direction in the development of such SO is SO with frequency-setting elements based on surface acoustic waves (SAW).Aim. A review of international achievements in the development of frequency-setting elements based on SAW and respective SO.Materials and methods. The selection of materials for a comparative analysis and generalization was carried out using available sources published over the past 30 years in well-known engineering journals, advertising brochures and websites of the manufacturers of devices based on SAW. The selection criteria included low values of the power spectral density of the frequency fluctuations of the generated signal, the presence of vibration protection, the presence of a thermostat, as well as the miniaturization and originality of the design.Results. Specific features of various methods used for constructing microwave oscillators were analyzed. It is shown that the achievement of the best values of the power spectral density of frequency fluctuations in SO with frequency-setting elements on SAW is possible only with the use of two-port resonators. An analysis of the main technical characteristics of temperature-controlled vibration-resistant SO was carried out.Conclusion. Despite the large number of different manufacturers on the world market (more than 20 companies) and the variety of different models of oscillators with frequency-setting elements on SAW (more than a 100 different models), only two companies produce oscillators resistant to external vibrations and acoustic noise.